Education in the climate emergency: school sustainability practices, climate imaginaries, and teaching hope - Finnegan, W (2023)
The Intergovernmental Panel on Climate Change has reported with very high confidence that human activity is changing the climate, that climate change has severe impacts for human and natural systems, and that we have a limited window to dramatically reduce greenhouse gas emissions and limit global warming to 1.5 °C. Our future is being shaped by this crisis and our collective responses to mitigate and adapt to it. This article-based thesis presents interdisciplinary research on the response of secondary schools in England to climate change. The chapters first introduce a doctoral journey over 3.5 years, including adaptations in response to COVID-19. They then present a combined literature review, weave together the three academic articles, and end by exploring the contributions of this research and sharing future plans. The first paper (Chapter 3) was based on a large number of semi-structured interviews and focus group conversations with different school stakeholders at both state and independent schools. Theories of social practice and practice architectures were used to explore bundles of practices and the arrangements that support them related to sustainability, especially in terms of semantic (sayings), material (doings) and social (relatings) dimensions. The article, currently under peer review by the journal Energy Research and Social Science, argued for expanding whole-school approaches to sustainability to incorporate insights from practice architectures. The second paper (Chapter 4) involved data collection through a questionnaire distributed to Sixth Form students and teachers, primarily comprising measures of action competence and climate hope that were previously developed and validated by other researchers. Quantitative analysis of this data revealed the relationship between teacher practices and student reported hope, and compared responses based on students from independent versus state schools and students that identified as female versus male. This article was published in the journal Environmental Education Research. The third paper (Chapter 5) used the creative, participatory method of speculative digital storytelling, in which 16-18-year-olds in the UK and Ireland participated in workshops to produce a short ‘letter from the future’ in a video format. Through reflexive thematic and narrative analysis, themes related to the scripts and visuals were identified, as well as different narratives of climate futures. This article was published in the journal Children’s Geographies. The discussion (Chapter 6) outlines three threads that weave together the research – education, futures, storytelling – and offers a series of methodological, theoretical and empirical contributions, including speculative digital storytelling, practice-informed whole-school sustainability, and hope-based pedagogies in climate education.